Effects of Natural Infestations of the Mite Varroa destructor on the Development of Africanized Honeybee Workers (Apis mellifera) - de Mattos, Igor Medici [UNESP]; Chaud-Netto, Jose [UNESP] (California State University, 2011)
The mite Varroa destructor (Anderson & Treuman 2000) has caused extensive damage to beekeeping worldwide. In Brazil, weather conditions and the strains of bees do not provide ideal conditions for mite parasitism, which is reflected in the low number of deaths of colonies caused by varroatosis well as the stability of infestation levels. The aim of this study was to evaluate the damage caused by the mite infestation in hives maintained in natural conditions. For this purpose the number of mites per bee was calculated and used to quantify the level of infestation in each colony. To record the mortality rates of parasitized bees during development daily checks were performed. The data were analyzed by G test of independence and a Test of Proportions. The results indicate that the rate of mortality of pupae and larvae was proportional to the degree of infestation in each colony, and all colonies showed mortality rates significantly higher than the control rate. A significant interaction among death rates recorded between the third and fourth days of larval life and the total death of larvae was found (G Test = 50.22; P < 0.0001). So, it can be concluded that bee inbreeding contributed significantly to the increase of the larval rate of mortality. In Africanized honeybee colonies infested by the mite Varroa destructor mortality rates in conditions of natural infestation varied from 6.65 to 9.89% in pupae (<(x)over bar>= 8.78%) and from 6.13 to 13.48% in larvae ((x) over bar = 9.91%), against 3.85% and 3.74% in the control colony, respectively. Therefore, in the infested colonies the average rates of mortality caused by the harmful effects of the mite were, respectively, 2.28 times and 2.65 times greater in those two developmental stages.
Keywords: Africanized honeybees; Apis mellifera; Varroa destructor; mortality analysis; development